Method to increase the yield of eukaryotic membrane protein expression in Saccharomyces cerevisiae for structural and functional studies. (2nd July 2014) - Parker, Joanne L.; Newstead, Simon
Abstract Despite recent successes in the structure determination of eukaryotic membrane proteins, the total number of structures of these important proteins is severely underrepresented in the Protein Data Bank. Although prokaryotic homologues provide valuable mechanistic insight, they often lack crucial details, such as post‐translational modification and additional intra or extracellular domains that are important for understanding the function and regulation of these proteins in eukaryotic cells. The production of milligram quantities of recombinant protein is still a serious obstacle to the structural and functional characterization of these proteins. Here, we report a modification to a previously described over expression system using the simple eukaryote Saccharomyces cerevisiae that can increase overall protein yield and improve downstream purification procedures. Using a metabolic marker under the control of a truncated promoter, we show that expression levels for several membrane transporters are increased fourfold. We further demonstrate that the increase in expression for our test proteins resulted in a concomitant increase in functional protein. Using this system, we were able to increase the expression level of a plant transporter, NRT1.1, which was a key factor in its structural and functional characterization.